Clinical Presentation and Management of Nephrolithiasis in the Obstetric Patient: A Matched Cohort Study [07N]. (May 2020) - Sebastian, Natasha; Abenhaim, Haim Arie; Spence, Andrea; Czuzoj-Shulman, Nicholas
Abstract : INTRODUCTION: Nephrolithiasis is a common medical condition, but little is known about its occurrence in pregnant patients. The study objective is to compare the clinical presentation and management of nephrolithiasis in pregnant women compared with non-pregnant women. METHODS: A retrospective matched-cohort study was conducted using the United States' Healthcare Cost and Utilization Project-Nationwide Inpatient Sample database from 1999 to 2015. ICD-9 coding was used to identify women with nephrolithiasis within this cohort. Pregnant women with nephrolithiasis were identified and age matched (1:1) to non-pregnant women with nephrolithiasis. Conditional logistic regression, adjusted for baseline characteristics, was used to compare the clinical presentation and management of nephrolithiasis in pregnant versus non-pregnant women. RESULTS: There were 30, 006 pregnant patients with nephrolithiasis in the cohort. Pregnant women, relative to non-pregnant women, were more likely to be treated in urban teaching hospitals and to have private health insurance. Pregnant patients were less likely to present with classic clinical symptoms of nephrolithiasis, such as flank pain, OR 0.48 (95% CI 0.45–0.53), hematuria, 0.79 (0.73–0.86), and fever, 0.17 (0.13–0.22). Pregnant patients displayed shorter lengths of stay in hospital (3 days or more, 0.81 (0.78–0.84) and were less likely to be affected by infectious conditions, namely urinary tract infections, 0.56 (0.53–0.58), sepsis, 0.14 (0.12–0.16), and pyelonephritis, 0.38 (0.36–0.42). All invasive and surgical procedures were more frequently practiced in the non-pregnant group. CONCLUSION: Pregnant women admitted with nephrolithiasis appear to have a milder disease course as compared to age-matched non-pregnant women, likely suggesting better access to care and a lower threshold for admission.